Can Culture Media Impact Preimplantation Embryo Aneuploidy? - Jason E. Swain (Fertility & Reproduction, 2021)
With continued improvements in blastocyst culture, cell sampling approaches, and genetic analysis platforms, the resulting improvements in embryo development and the resolution and accuracy of chromosome analysis have provided valuable insights into the preimplantation embryo. This includes the impact of in vitro culture conditions on chromosomal dynamics. Specifically, through analysis of embryo aneuploidy and mosaicism, a growing number of reports indicate that rates of chromosomal abnormalities can vary between IVF centers. Because differences in mosaicism reflect mitotic errors, this endpoint analysis suggests that IVF laboratory-controlled variables during embryo development may be influencing chromosome separation and segregation. A growing body of literature suggests that culture media may be one variable influencing preimplantation embryo aneuploidy and mosaicism. However, these data are far from definitive in demonstrating cause-and-effect. Whether reported differences may be due to media formulation, use of sequential media or single-step media, or uninterrupted culture approaches is unknown. Importantly, variables directly impacting media performance and embryo development, including pH, temperature, osmolality, and oxygen concentration, must also be considered and make it difficult to isolate the impact of culture media as the sole factor responsible. These IVF laboratory variables will be reviewed and literature suggesting a possible link to mitotic aneuploidy/mosaicism will be discussed.